Effect of different parameters on the hydrolytic activity of cross-linked enzyme aggregates (CLEAs) of lipase from Thermomyces lanuginosa - Guauque Torres, María del Pilar (2013)
Cross-linked enzyme aggregates (CLEAs) of lipase from Thermomyces lanuginosa (TLL) were synthesized using (NH4)2SO4 as precipitant and glutaraldehyde as cross-linking agent. CLEAs were assayed for their hydrolytic activity in a reaction performed in an emulsioned medium. The effects of the amount of precipitant, cross-linker, and different additives such as protein cofeeder, oleic acid, n-heptane, sodium dodecyl sulfate (SDS), polyethylenglicol (PEG) and ethylendiamine were studied at selected ratios with respect to TLL mass. Traditional non-layered CLEAs of TLL showed recovered activities between 3 and 31% when compared with native lipase. Novel TLL layered CLEAs consisting of a protein cofeeder core and successive layers of target lipase showed an important increase in their retained activity. The highest recovered activity was found for the one-layered non-additivated CLEAs of TLL which showed a recovered activity of 75%.